IgG4-Related Disease With Tuberculosis: A Case Report and Retrospective Review of Patients in a Single Center - Qing, Pingying; Lu, Chenyang; Liu, Zhihui; Wen, Xiuzhen; Chen, Bo; Lin, Zhiguo; Ma, Yingbing; Zhao, Yi; Liu, Yi; Tan, Chunyu (Frontiers in Immunology, 2021)
Background: IgG4-related disease (IgG4-RD) is a recently recognized systemic fibro-inflammatory disease of unknown cause involving many organs including pancreas, salivary glands, and lymph nodes. Chronic tuberculosis (TB) infection has been reported in IgG4-RD, but the prevalence of TB infection has not been evaluated in IgG4-RD. Methods: Characterization of a patient with IgG4-RD by physical examination, laboratory tests, magnetic resonance imaging (MRI) and histological examination. TB infection was evaluated by medical history, radiological examinations, sputum examinations, tubercular skin test (TST) and interferon gamma release assay test (IGRA). Medical records of IgG4-RD patients were reviewed in our institute from February 2015 to September 2020 to explore the prevalence of TB infection in IgG4-RD. Results: We described a 40-year-old Chinese man presented with headache and diplopia. Physical examination revealed bitemporal hemianpsia and limited abduction of both eyes. MRI revealed uniformly enhancing mass overlying clivus with dural tail sign. Laboratory data revealed elevation of IgG4 (1.9g/L), and TB-IGRA demonstrated significantly elevated IFN-γ (414.21 pg/ml). The clivus lesion was subtotally removed and IgG4 was strongly positive on immunohistochemical staining. The diagnosis of IgG4-RD was established, and the patient received treatment of corticosteroids, methotrexate, and cyclophosphamide with isoniazid prophylaxis. Consequently, the mass shrank remarkably within 3 months. A similar concurrence of TB disease or latent TB infection (LTBI) and IgG4-RD was present in 17/47 (36.2%) patients in our institute. Conclusion: High frequency of TB/LTBI presented in patients with IgG4-RD. Patients with IgG4-RD and LTBI should be closely monitored for resurgence of TB. Whether TB represents a risk for IgG-4RD should be further investigated in prospective cohort.